HUBUNGAN USIA IBU HAMIL DENGAN KEJADIAN PLASENTA PREVIA DI RUMAH SAKIT CAMATHA SAHIDYA KOTA BATAM - Suryanti .; Ferry Daniel Martinus Sihombing (Universitas Batam, 2019)
One of the causes of bleeding during pregnancy is placenta previa, which is the placenta that covers all or part of the internal uterine ostium. One of the risk factors for placenta previa is Age because it can cause sclerosis of small arteries and myometrial arterioles which causes uneven blood flow to the endometrium so that the placenta grows wider with a larger surface area. So the researchers wanted to look for a relationship between maternal age and placenta previa. This research method is analytic observational with a cross-sectional approach conducted at the Camatha Sahidya Hospital in Batam City in 2019. Data is taken from the patient's medical record from June 1 to June 31, 2019. The sampling technique is total sampling where the number of samples is the same with a population of 135 people in June 2019. The results of the study were analyzed by frequency distribution in a cross-tabulation then tested by Chi-square test. The results of this study showed that out of 135 mothers, 4 mothers (17.4%) out of 23 mothers aged> 35 years were declared into the Placenta Previa group and 19 mothers (82.6%) out of 23 mothers aged> 35 years were stated in the group. No Placenta Previa. And obtained 112 mothers aged 20-35 years from 135 mothers in which there were 2 mothers (1.8%) who were stated in the Placenta Previa group and 110 mothers (98.2%) stated in the No Placenta Previa group. Chi-Square analysis results obtained significance value p = 0.008. This figure is significant because the p-value is smaller than the significance level (ï¡) = 5% (0.05). Therefore it can be concluded that there is a significant relationship between maternal age and the incidence of placenta previa. Based on this study it can be concluded that there is a significant relationship between maternal age and the incidence of placenta previa.